2021
DOI: 10.1136/bjsports-2020-103622
|View full text |Cite
|
Sign up to set email alerts
|

Medical care and first aid: an interassociation consensus framework for organised non-elite sport during the COVID-19 pandemic

Abstract: The cessation of amateur and recreational sport has had significant implications globally, impacting economic, social and health facets of population well-being. As a result, there is pressure to resume sport at all levels. The ongoing prevalence of SARS-CoV-2 and subsequent ‘second waves’ require urgent best practice guidelines to be developed to return recreational (non-elite) sports as quickly as possible while prioritising the well-being of the participants and support staff.This guidance document describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Multiple studies have reported on the clinical patterns of COVID-19 in athletic populations and provide valuable frameworks for optimal athlete recovery and care moving forward. 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Iievolution Of Telehealth and Virtual Physical Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported on the clinical patterns of COVID-19 in athletic populations and provide valuable frameworks for optimal athlete recovery and care moving forward. 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Iievolution Of Telehealth and Virtual Physical Examinationsmentioning
confidence: 99%
“…Recommendations from team physicians have also advocated for training at outdoor or well-ventilated indoor facilities, and travel bans were initially established to reduce transmission between athletes. 23 , 24 For screening prevention, daily self-reported symptom checklists and fever monitoring may help identify potentially infected athletes who should then be instructed to isolate immediately and seek medical care. RNA detection polymerase chain reaction (PCR) testing for the virus via nasopharyngeal swab is not recommended as a screening measure and should be reserved for symptomatic individuals presenting with fever, cough, or shortness of breath.…”
Section: Iievolution Of Telehealth and Virtual Physical Examinationsmentioning
confidence: 99%
“…Reducing the duration and frequency of interactions can be effective, as clinical environments tend to be specialised and not easily relocated to optimise environmental conditions. National healthcare guidance on personal protective equipment (PPE) has been interpreted for the sporting setting, taking into account the sport-specific nature, including delivery of pitch-side medical care (Table 1), [84,85] with the recommendation that athlete patients also wear a face covering for the duration of review. [82] Safe and effective use of PPE is founded on good training to ensure it is worn correctly and the risk of self-contamination is minimised during application and removal (donning and doffing).…”
Section: Providing Safe Medical and Professional Carementioning
confidence: 99%
“…Depending on resource availability and staff familiarity with donning and doffing, organisations may wish to have staff already prepared in Level 3 PPE for high-risk settings in order to prevent any unnecessary delay in delivering prompt emergency care. [84,85] In circumstances where only Level 2 PPE is available, or there is a delay in donning Level 3 PPE, airway interventions beyond simple manoeuvres are not recommended. In cardiopulmonary resuscitation (CPR), chest compressions can be commenced in addition to the use of an automated external defibrillator, provided that a face covering is applied to the casualty which does not impede airflow (i.e.…”
Section: Providing Safe Medical and Professional Carementioning
confidence: 99%
See 1 more Smart Citation